Production and catalytic properties of amylases from Lichtheimia ramosa and Thermoascus aurantiacus by solid-state fermentation - De Oliveira, Ana Paula Aguero; Silvestre, Maria Alice; Garcia, Nayara Fernanda Lisboa; Alves-Prado, Heloíza Ferreira [UNESP]; Rodrigues, André [UNESP]; Paz, Marcelo Fossa Da; Fonseca, Gustavo Graciano; Leite, Rodrigo Simões Ribeiro (Hindawi, 2016)
The present study compared the production and the catalytic properties of amylolytic enzymes obtained from the fungi Lichtheimia ramosa (mesophilic) and Thermoascus aurantiacus (thermophilic). The highest amylase production in both fungi was observed in wheat bran supplemented with nutrient solution (pH 4.0) after 96 hours of cultivation, reaching 417.2 U/g of dry substrate (or 41.72 U/mL) and 144.5 U/g of dry substrate (or 14.45 U/mL) for L. ramosa and T. aurantiacus, respectively. The enzymes showed higher catalytic activity at pH 6.0 at 60°C. The amylases produced by L. ramosa and T. aurantiacus were stable between pH 3.5-10.5 and pH 4.5-9.5, respectively. The amylase of L. ramosa was stable at 55°C after 1 hour of incubation, whereas that of T. aurantiacus maintained 60% of its original activity under the same conditions. Both enzymes were active in the presence of ethanol. The enzymes hydrolyzed starch from different sources, with the best results obtained with corn starch. The enzymatic complex produced by L. ramosa showed dextrinizing and saccharifying potential. The enzymatic extract produced by the fungus T. aurantiacus presented only saccharifying potential, releasing glucose monomers as the main hydrolysis product.